2015
DOI: 10.3109/01902148.2014.985407
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary edema measured by MRI correlates with late-phase response to allergen challenge

Abstract: We show a temporal relationship between edema and the LAR and their parallel reduction, along with eosinophils and AHR, by dexamethasone. This suggests a close causative association between pulmonary edema and impaired airways function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…5C), which showed no differences in mRNA expression between WT and Chi3l1 À/À mice. Though more commonly measured in acute lung injury, pulmonary edema can also contribute to AHR in animal models (34) and is present in very severe clinical cases of asthma (35). We analyzed wet/dry ratios of WT and Chi3l1 À/À mice and observed decreased ratios in the latter during fungal asthma.…”
Section: Chitinase 3-like-1/brp-39 Deficiency Does Not Affect Productmentioning
confidence: 99%
“…5C), which showed no differences in mRNA expression between WT and Chi3l1 À/À mice. Though more commonly measured in acute lung injury, pulmonary edema can also contribute to AHR in animal models (34) and is present in very severe clinical cases of asthma (35). We analyzed wet/dry ratios of WT and Chi3l1 À/À mice and observed decreased ratios in the latter during fungal asthma.…”
Section: Chitinase 3-like-1/brp-39 Deficiency Does Not Affect Productmentioning
confidence: 99%
“…MRI was increasingly applied also in patients with asthma, demonstrating the occurrence of segmental lung edema and being a robust method for monitoring the response to treatment. [164][165][166][167]. Furthermore, it has been shown that hyperpolarized gases allow the evaluation of functional changes in distal small airways of asthmatic patients.…”
Section: Magnetic Resonance Imaging (Mri) and Pet/mrimentioning
confidence: 99%